Research into the Value of B-Mode Ultrasound, CT and MRI Examinations in the Diagnosis of Preoperative Myometrial Infiltration of Endometrial Cancer and Lymph Node Metastasis - Lu Ren; Guixia Sun (Open Medicine, 2015)
This study is conducted to observe the diagnostic value of B-mode ultrasound, CT and MRI examinations in preoperative myometrial infiltration of endometrial cancer and lymph node metastasis. Retrospectively analyze 50 cases of the patients from Oct. 2010 to Aug. 2013. Before operation all the patients received dilatation & curettage to determine pathological diagnosis and clinical staging. There were 150 cases of patients who received B-mode ultrasound examination, wherein, 93 cases received CT examination and 57 cases received MRI examination as well. In the diagnosis of MIEC the diagnostic indicies of individual MRI examination were higher than that of individual B-mode ultrasound and CT examinations. Consistency of individual MRI examination with pathological diagnosis was significantly higher than that of B-mode and CT examinations. The sensitivity of CT and MRI was significantly higher than that of B-mode ultrasound examination. However, diagnostic indicators of B-mode ultrasound and CT joint examination were higher than B-mode ultrasound examination alone. The consistency of both with pathological diagnosis was significantly increased. B-mode and CT can significantly improve the diagnostic accuracy and has a good consistency with pathological diagnosis, thereby applicable to the clinical diagnosis of preoperative myometrial infiltration of endometrial cancer and lymph node metastasis.